Tumor immune microenvironment and immune checkpoint inhibitors in esophageal squamous cell carcinoma - Baba, Yoshifumi; Nomoto, Daichi; Okadome, Kazuo; Ishimoto, Takatsugu; Iwatsuki, Masaaki; Miyamoto, Yuji; Yoshida, Naoya; Baba, Hideo (Cancer science, 2020)
Esophageal squamous cell carcinoma (ESCC) is the main prevalent histological type of esophageal cancer, predominantly constituting 90% of cases worldwide. Despite the development of multidisciplinary therapeutic approaches, its prognosis remains unfavorable. Recently, the development of monoclonal antibodies inhibiting programmed death 1 (PD‐1) or programmed death‐ligand 1 (PD‐L1) has led to marked therapeutic responses among multiple malignancies including ESCC. However, only a few patients achieved clinical benefits due to resistance. Therefore, precise and accurate predictive biomarkers should be identified for personalized immunotherapy in clinical settings. Because the tumor immune microenvironment can potentially influence the patient's response to immune checkpoint inhibitors, tumor immunity, such as PD‐L1 expression on tumors, tumor‐infiltrating lymphocytes, tumor‐associated macrophages, and myeloid‐derived suppressor cells, in ESCC should be further investigated. In this review, accumulated evidence regarding the tumor immune microenvironment and immune checkpoint inhibitors in ESCC are summarized. Because the tumor immune microenvironment can potentially influence the patient's response to immune checkpoint inhibitors, tumor immunity, such as PD‐L1 expression on tumors, tumor‐infiltrating lymphocytes, tumor‐associated macrophages, and myeloid‐derived suppressor cells, in ESCC should be further investigated. In this review, accumulated evidence regarding the tumor immune microenvironment and immune checkpoint inhibitors in ESCC are summarized.